Effects of different charging and discharging strategies of electric vehicles under various pricing policies in a smart microgrid. (25th April 2019) - Vokas, Georgios A.; Anastasiadis, Anestis G.; Kondylis, Georgios P.; Polyzakis, Apostolos
Nowadays, the effects of the incorporation of electric vehicles (EVs) have to be taken into consideration with care, since it may result in unfeasible operations for the grids (especially for the Smart Microgrids). Smart microgrids (SMs) seem to be the best solution for the management of modern low voltage (LV) grids with distributed energy resources (DER). The main purpose of this paper is to investigate the effects of different EVs' charging and discharging strategies in a SM. With EVs and absence of DERs and therefore satisfaction of the full load from the upstream network, is considered as the base case. For each scenario, six different charging technologies are examined. In addition, three different pricing policies based on system marginal price (SMP) are considered. All different cases are compared between them to determine which one is the most advantageous in terms of operational cost.